2016
DOI: 10.1111/afe.12203
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cues potentially mediating host selection ofLeptoglossus occidentalisonPinus contorta

Abstract: 1 Leptoglossus occidentalis causes significant damage in conifer seed orchards. Host selection by L. occidentalis is not completely understood. Earlier research has demonstrated a preference for certain clones of Pinus contorta, indicating that L. occidentalis responds to chemical or physical cues. 2 The present study aimed to test whether L. occidentalis shows clonal preference across years, and to examine whether the host cues responsible for this could be identified. 3 Surveys were conducted in a lodgepole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…A survey of seven seed orchards in the Province of BC detected variable levels of seed viability accompanied by an increase in the incidence of fungal colonization in mature seed of lodgepole pine. While all seed orchards demonstrated substantial fungal colonization of seeds in maturing cones, only those six orchards located in southern BC showed a significant decline in to constitute a substantial percentage of the remaining portion (Richardson et al 2016). Abiotic factors, such as high temperatures, may have an influence (Woods 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of seven seed orchards in the Province of BC detected variable levels of seed viability accompanied by an increase in the incidence of fungal colonization in mature seed of lodgepole pine. While all seed orchards demonstrated substantial fungal colonization of seeds in maturing cones, only those six orchards located in southern BC showed a significant decline in to constitute a substantial percentage of the remaining portion (Richardson et al 2016). Abiotic factors, such as high temperatures, may have an influence (Woods 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We know that external agents can be responsible for catastrophic seed losses. A seed-destroying insect pest, Leptoglossus occidentalis, is known to diminish seed yield (Richardson et al 2016). Internal factors in the host, such as selfing have also been proposed (Owens et al 2005), but have been ruled out by genetic testing (Michael Carlson pers.…”
Section: )mentioning
confidence: 99%
“…Blatt and Borden () revealed a clonal preference in seed orchards of Lodgepole pine and Douglas‐fir and Richardson et al . () demonstrated that cone terpenes and cone size may also play an important role in the selection of the host by this bug species. Studies on cues mediating mature seed selection do not exist.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the selection of the tree, the bug tends to select vigorous trees, i.e. denser canopies and longer needles, (Farinha et al 2018b) bearing moderate crops because it is usually a sign of having larger cones and therefore larger seeds (Blatt 1997, Blatt and Borden 1999, Richardson et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Although feeding on a wide range of conifers, L. occidentalis seems capable of distinguishing between clones of P. contorta (Blatt and Borden 1996, Richardson et al 2017 and between cones of P. pinea of different physiological status (Farinha et al 2018b). This host selection capability strongly indicates that the bug can probably discriminate between different host conifers.…”
Section: Introductionmentioning
confidence: 99%